POTENSI KESUBURAN TANAH TANAMAN KOPI ROBUSTA DAN PETA PENYEBARANNYA MENGGUNAKAN APLIKASI GIS DI KECAMATAN KINDANG - Jayadi, Muh.; Rismaneswati, Rismaneswati; Irawan, Okky (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Kindang District is an allotment area for robusta coffee plantations. In terms of climate, Kindang District has the potential to produce high coffee production. However, there was a decrease in coffee production. Therefore, it is necessary to analyze the potential of soil fertility related to biophysical aspects for the development of robusta coffee plants based on land suitability. This study aims to analyze the potential for soil fertility based on land suitability for robusta coffee. This research method uses a descriptive method and determines the land suitability index using the square root approach. Profile observations were made at 11 points spread across the Kindang District. The results of this study indicate that the land in Kindang District belongs to the marginal land suitability class (S3) for robusta coffee with a land suitability index value between 25.51-45.18. The limiting factors found were slope, soil depth and soil pH with an area of ​​9,660 ha.